1989
DOI: 10.1042/bj2620597
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of the suicide inactivation of an enzyme measured through coupling reactions. Application to the suicide inactivation of tyrosinase

Abstract: A systematic procedure for the kinetic study of reaction mechanisms with enzyme inactivation induced by a suicide substrate in the presence or in the absence of an auxiliary substrate, when the enzyme activity is measured through coupling reactions, enzymically catalysed or not, was developed and analysed by using the transient-phase approach. The methodology is established to determine the parameters and kinetic constants corresponding to the enzyme suicide inactivation and the coupling reactions. This approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…For 3-chlorocatechol, DHB was used as a reporter substrate, and j 3E app was obtained using Equation 5 (48).…”
Section: Partition Ratio ϭmentioning
confidence: 99%
“…For 3-chlorocatechol, DHB was used as a reporter substrate, and j 3E app was obtained using Equation 5 (48).…”
Section: Partition Ratio ϭmentioning
confidence: 99%
“…dium (21)(22)(23)(24). However, to our knowledge, the progress and are comparable to those defined by the dilution assay method of suicide inhibitors (see Appendix for curve kinetic analysis method for suicide inhibitors has not been applied to the most common case (most com-the definition of these parameters).…”
mentioning
confidence: 80%
“…MT has been frequently studied with regard to its suicide substrate inactivation [21][22][23] and stability [24,25]. It was recently shown that the Tyr residues spatial arrangement plays a noticeable role in the efficiency of the MT activities [25].…”
Section: Introductionmentioning
confidence: 99%